Estudo da atividade antibacteriana do Isoeugenol contra cepas clínicas de Pseudomonas aeruginosa - Galvão, José Lucas Ferreira Marques (2019)
Scientific evidence over time shows that Pseudomonas aeruginosa stands out among gram-negative, non-fermenting bacteria that promote high rates of morbidity, mortality and increased hospital costs worldwide. This microorganism is intrinsically resistant to the wide diversity of substances, being able to become resistant to several antimicrobial agents. There is now a significant limitation of the therapeutic arsenal that can be used to treat infections caused by this multiresistant bacterium, since Pseudomonas aeruginosa can develop resistance mechanisms during this therapy. Therefore, based on the resistance promoted by this bacterium, the researchers' attention is drawn to the possibility of the use of natural compounds, being these, medicinal plants and essential oils and their phytoconstituents in the prevention or treatment of diseases, among these phyto-constituents, , a phenylpropanoid. In this study, the antibacterial activity of isoeugenol against clinical strains of Pseudomonas aeruginosa was evaluated by means of in vitro assays: Determination of Minimum Inhibitory Concentration (MIC) and Minimum Bactericidal Concentration (MBC) and studies of the association of isoeugenol with conventional antimicrobials (gentamicin and meropenem). In the evaluation of the antibacterial activity, two standard strains and ten strains of microbial strains were used, isoeugenol had a MIC of 64 μg / mL and a CBM of 128 μg / mL, whereas for conventional antimicrobials gentamicin had an MIC of 1024 μg / mL and a CBM> 1024 μg / mL, whereas meropenem had its MIC and MBC of 32 μg / mL. The combination of phenylpropanoid with gentamicin showed a synergistic effect for both the standard strain and the microbial strain 297, whereas it was observed that the association of meropenem with the standard strain resulted in an additive or indifference effect and for the strain of microbial strain 297 an antagonistic effect. Therefore, the results obtained in this study suggest an antibacterial activity of isoeugenol against clonal strains of P. aeruginosa, either alone or in combination with standard antimicrobial agents.